2011
DOI: 10.1103/physrevb.83.220402
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally strong magnetism in the 4dperovskitesRTcO3(et al.

Abstract: The evolution of the magnetic ordering temperature of the 4d 3 perovskites RTcO 3 (R = Ca, Sr, Ba) and its relation with its electronic and structural properties has been studied by means of hybrid density functional theory and Monte Carlo simulations. When compared to the most widely studied 3d perovskites the large spatial extent of the 4d shells and their relatively strong hybridization with oxygen weaken the tendency to form Jahn-Teller like orbital ordering. This strengthens the superexchange interaction.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 37 publications
7
58
0
Order By: Relevance
“…As any functional, does not necessary gives better results. [26] These will make subject for each oxide separately. For the study of some oxides like Mn 3 O 4 , Mn 2 O 3 , and CoO 4 , other approximations for the exchange and correlations effects could be imposed, such as DFT+U.…”
Section: Methodsmentioning
confidence: 99%
“…As any functional, does not necessary gives better results. [26] These will make subject for each oxide separately. For the study of some oxides like Mn 3 O 4 , Mn 2 O 3 , and CoO 4 , other approximations for the exchange and correlations effects could be imposed, such as DFT+U.…”
Section: Methodsmentioning
confidence: 99%
“…For these calculations, the HSE06 with 25% exact exchange was used, which had been shown to accurately describe the electronic structure of various crystalline phases of MnO 2 [24,53] and to accurately predict defect levels. [54] In order to model the electronic structure in a manner consistent with experimental operating temperatures and with the experimental observation of a Néel temperature well below 100 K for spinel LiMn 2 O 4 , [55] a constraint of low total spin was imposed by restricting calculations to spin configurations with low net spin.…”
Section: Methods Sectionmentioning
confidence: 99%
“…A more detailed discussion of the role of α on the ground state properties of magnetic oxide perovskites can be found in [81]. In the last few years, the application of hybrid functionals to a wide class of solid state systems, including ferroelectrics [82][83][84], multiferroics [16,65,66] and magnetic perovskites [81,85] has shown that an improved description of ground state structural, electronic and magnetic properties with respect to the standard GGA and GGA+U can be achieved, in general. Due to the high computational cost of HSE calculations, the Fock exchange was sampled using the twofold reduced k-point grid.…”
Section: Methodsmentioning
confidence: 99%